Effect of various soil amendments and moisture regimes on nutrient availability in a light textured soil in rice-wheat cropping system in eastern Bihar - SINGH, YANENDRA KUMAR; PRASAD, R.; KUMAR, RAKESH; SHAMBHAWI, SHWETA; KUMAR, RAJESH; KUMAR, SHASHI BHUSHAN (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted on a calcareous soil to find out the effect of flyash (FA) and sulphitation press mud (SPM) on soil nutrient availability at different irrigation regime under rice-wheat cropping system. Light textured soils suffer from poor soil conditions like poor nutrient retention capacity and nutrient release characteristics which ultimately result in poor crop yields. Application of flyash and sulphitation press mud alone or in combination and pond soil resulted in an increase in organic carbon content and available nitrogen, phosphorus and potash content of soil as compared to control. The trend for this increase followed the SPM+FA > SPM > FA > pond soil for organic carbon and available nitrogen and phosphorus whereas for available potash the trend was SPM+FA > FA > SPM > pond soil. Changing the soil moisture regime with irrigation did not significantly influence the soil chemical characteristics.